2022
DOI: 10.1002/prp2.975
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of β‐adrenoceptors in the cardiovascular responses induced by selective adenosine A2A and A2B receptor agonists

Abstract: A2A and A2B adenosine receptors produce regionally selective regulation of vascular tone and elicit differing effects on mean arterial pressure (MAP), whilst inducing tachycardia. The tachycardia induced by the stimulation of A2A or A2B receptors has been suggested to be mediated by a reflex increase in sympathetic activity. Here, we have investigated the role of β1‐ and β2‐adrenoceptors in mediating the different cardiovascular responses to selective A2A and A2B receptor stimulation. Hemodynamic variables wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Interestingly, after the use of an A 2A R agonist, the increase in the heart rate was attenuated by a β-blocker. Thus, Wragg et al demonstrated a direct activation of the sympathetic nervous system by A 2A R stimulation [ 171 ].…”
Section: Association Between Atrial Fibrillation Risk Factors and The...mentioning
confidence: 99%
“…Interestingly, after the use of an A 2A R agonist, the increase in the heart rate was attenuated by a β-blocker. Thus, Wragg et al demonstrated a direct activation of the sympathetic nervous system by A 2A R stimulation [ 171 ].…”
Section: Association Between Atrial Fibrillation Risk Factors and The...mentioning
confidence: 99%